Well drilling composite lubricating material

By using multi-layer composite lubricating materials in drilling fluid, the problem of drilling liquid lubricating materials failing during high temperatures and circulation processes is solved, and the fixed-point release of lubricant and heat absorption cooling is achieved, reducing the foaming rate and improving the Stability and lubricating properties of drilling fluid.

CN119193118AActive Publication Date: 2024-12-27SOUTHWEST PETROLEUM UNIV +1

Patent Information

Application Number
CN202411324043.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-23
Publication Date
2024-12-27
Estimated Expiration
2044-09-23

AI Technical Summary

Technical Problem

Existing drilling liquid lubricating materials are prone to failure during high temperatures and circulation, resulting in an increase in friction coefficient and an increase in bubble rate, affecting the density and safety of drilling fluid, and low lubricant utilization rate.

Method used

Using composite lubricating materials composed of liquid lubricant, inorganic protective shell layer, phase change layer and smooth outer shell layer, the multi-layer structure is isolated and heat-absorbing and cooling to ensure that the lubricant maintains performance in high-temperature environments and is fixed at high friction areas. release.

Benefits of technology

It effectively alleviates the adhesion loss and high-temperature failure of lubricants in non-key parts underground, reduces the foaming rate, improves the utilization rate of lubricants and the stability of drilling fluid, and ensures low friction and efficient lubrication during drilling.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119193118A_ABST
    Figure CN119193118A_ABST
Patent Text Reader

Abstract

The invention discloses a composite lubricating material for well drilling. The composite lubricating material comprises a core layer, a protective shell layer, a phase change layer and a smooth shell layer which are sequentially wrapped from inside to outside to form micron-sized spheres, the core layer is a liquid lubricant, the protective shell layer is an inorganic protective shell layer, the phase change layer is prepared from a solid-liquid conversion phase change material, and the smooth shell layer is prepared from an inert material. By utilizing the four-layer structure of the composite lubricating material for well drilling, the composite lubricating material can be attached to a key part with serious friction loss in a fixed point manner to play a lubricating role, and can maintain low foaming property and high lubricating property after repeatedly entering an underground high-temperature environment, so that technical support is provided for well drilling construction operation.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of lubricating materials, and in particular to a composite lubricating material for drilling. Background Art

[0002] With the opening of the "10,000-meter era" of exploration wells in my country, the requirements for drilling technology are also constantly increasing. During the drilling operation, friction will continue to occur between the drill bit and the rock and casing. The friction will increase the rotation resistance of the drill bit, making it difficult to start and drill. Excessive rotation resistance of the drill bit will also cause the drill bit to vibrate, which may cause the drill bit to break and the wellbore to become unstable, making it impossible to carry out the drilling work normally, causing huge economic losses. The friction mechanism in the drilling process originates from the boundary friction and fluid friction of the contact between two solid surfaces. Fluid friction is caused by the viscosity of the fluid between the friction surfaces, and the friction coefficient is usually small. Boundary friction is the main source of friction in drilling. In view of the boundary friction mechanism, the friction coefficient and wear in the drilling process are mainly reduced by adding lubricating materials to the drilling fluid. Lubricating materials can form an adsorption film or reaction film on the friction surface, converting the friction between the rough surfaces into friction between the adsorption films, thereby reducing the friction torque between the drill bit and the well wall and the friction coefficient of the drilling fluid filter cake, effectively improving the hydraulic power of the drill bit, and preventing the occurrence of pressure support, drill jamming and other phenomena.

[0003] Commonly used drilling lubricants include solid lubricants and liquid lubricants. Among them, solid lubricants can isolate friction surfaces and reduce friction and wear. They can convert sliding friction between friction surfaces into rolling friction in the form of spheres or can be adsorbed on friction surfaces in the form of sheet structures, converting friction between friction surfaces into sliding friction between sheet structures. Since the atoms of a single sheet of a layered material are bound by covalent bonds, but the sheets are connected by weak van der Waals interactions. Therefore, the shear resistance of sliding between layered lubricants is very low, which can reduce friction. Liquid lubricants are generally amphiphilic compounds based compounds, and their common structure is a linear alkyl chain with one or more polar functional groups connected to one end. Through the adsorption of polar groups on the friction surface and the dense arrangement of non-polar ends on the friction surface, the friction surfaces are effectively prevented from contacting each other. In the process of sliding against each other, the surface of this densely arranged layer of linear alkyl long chains has extremely low friction resistance, and its effect in reducing the friction coefficient is significantly better than that of solid lubricants (generally 1-2 orders of magnitude higher). In addition, for environmental protection purposes and to reduce the impact of the fluorescence of lubricating materials on logging, liquid lubricating materials are currently mainly used as drilling lubricants in drilling operations.

[0004] However, the liquid lubricating materials widely used at present are dispersed in the drilling fluid and then circulated into the system through the drilling fluid to play a lubricating role. During the circulation process, a large amount of lubricating materials will adhere to the parts that do not need lubrication, resulting in a large amount of material loss. Commonly used ester drilling liquid lubricants are prone to hydrolysis under formation temperature and alkaline conditions, which greatly increases the foaming ability of the lubricant. Due to the high concentration of lubricants in the drilling fluid system, a large amount of drilling fluid foaming occurs, resulting in a large density difference between the inlet and outlet of the drilling fluid, affecting normal drilling and drilling fluid level monitoring and the efficiency of the mud pump, and may even cause well control safety problems, increasing downhole safety risks. In addition, when the lubricating material circulates to the deep well, it will gradually lose its optimal lubrication performance or even completely lose its lubrication ability due to the high temperature environment. Summary of the invention

[0005] In view of the above problems, the present invention aims to provide a composite lubricating material for drilling.

[0006] The technical solution of the present invention is as follows:

[0007] A drilling composite lubricating material, comprising a core layer, a protective shell layer, a phase change layer and a smooth outer shell layer, which are sequentially wrapped from the inside to the outside to form a micron-sized spherical object;

[0008] The core layer is a liquid lubricant, the protective shell layer is an inorganic protective shell layer, the phase change layer is made of a solid-liquid conversion phase change material, and the smooth outer shell layer is made of an inert material.

[0009] Preferably, the liquid lubricant is any one of a modified vegetable oil lubricant, a polyol ester lubricant, an alcohol ether lubricant, a phosphate ester lubricant, and a mineral oil lubricant.

[0010] Preferably, the inorganic material of the inorganic protective shell layer is silicon dioxide or calcium carbonate.

[0011] Preferably, the solid-liquid phase change material is any one of paraffin, fatty acid, polyol, molten salt and hydrated salt.

[0012] Preferably, the inert material is any one of epoxy resin, vinyl ester resin, phenolic resin, urea-formaldehyde resin, melamine resin, polymethyl methacrylate, and natural polysaccharide derivatives.

[0013] Preferably, when the protective shell layer is a silica inorganic protective shell layer and the smooth shell layer is a urea-formaldehyde resin polymer shell layer, the drilling composite lubricating material is prepared by the following steps:

[0014] S1: 10-30 g of a liquid lubricant is mixed with 5-15 g of a tetraethyl silicate solution to obtain an oil phase, and the oil phase is added to 200-400 g of an ionic surfactant solution to react to obtain particles of the liquid lubricant coated with silica;

[0015] S2: subjecting the silica-coated liquid lubricant particles to a hydrophobic treatment to obtain silica-encapsulated particles having a hydrophobic surface;

[0016] S3: adding 20-30 g of urea and 50-70 g of formaldehyde to 500 g of water, dropping triethanolamine to adjust the pH to 8-9, then heating in a water bath at 60-70° C. for 40-90 min, and cooling to obtain a polymer shell prepolymer solution;

[0017] S4: heating the solid-liquid conversion phase change material to convert it into a liquid state to obtain a liquid phase change material; placing the silicon dioxide encapsulated particles having a hydrophobic surface in the liquid phase change material, and ultrasonically dispersing to obtain a dispersion;

[0018] S5: spraying the dispersion into the polymer shell prepolymer solution by a droplet jetting method, and using the temperature of the polymer shell prepolymer solution to solidify the liquid phase change material and adhere to the surface of the silica encapsulated particles having a hydrophobic surface;

[0019] S6: adjusting the pH of the mixed solution obtained in step S5 to 3-4, then heating it at 50-70° C. with stirring for 2-5 hours, and washing it to obtain the drilling composite lubricating material.

[0020] Preferably, in step S1, the solvent of the tetraethyl silicate solution is dichloromethane with a concentration of 10%.

[0021] Preferably, in step S1, the solute weight ratio of the ionic surfactant solution is 0.3-1%.

[0022] Preferably, in step S1, when reacting, first stir at a rotation speed of 1000-1500 r / min for 20-40 min, then heat to 40-50° C. and stir for 1.5-3 h, then adjust the pH value to 2-3, and finally heat to 75-85° C. and stir for 30 min to obtain the silica-coated liquid lubricant particles.

[0023] Preferably, in step S6, stirring is performed at a rotation speed of 800 to 1200 r / min; and during washing, anhydrous ethanol and deionized water are used in sequence for washing.

[0024] The beneficial effects of the present invention are:

[0025] The drilling composite lubricating material of the present invention is a micron-sized spherical particle with a four-layer structure that is coated step by step. It can absorb heat and cool the liquid lubricant in the core layer during the circulation of the drilling fluid system. The outermost smooth shell layer has a certain strength and can provide mechanical protection for the internal materials. The phase change material of the second layer can absorb heat by transforming from solid to liquid in the deep high-temperature area, and release the absorbed heat when circulating to the wellhead, thereby cooling the internal liquid lubricant when circulating to the well again. This multi-layer structure can effectively alleviate the problems of adhesion loss and high-temperature failure of liquid lubricants in non-critical lubrication parts underground.

[0026] The inorganic protective shell isolates the core liquid lubricant and the phase change material of the phase change layer, reducing the risk of the phase change material failing to effectively solidify and release heat in low-temperature areas after absorbing heat and converting to liquid and fusing with the liquid lubricant, thereby ensuring that the phase change material maintains good performance after multiple cycles of heat absorption and release.

[0027] The smooth outer shell of the composite lubricating material only breaks after being subjected to high shear stress at the high friction part to release the core liquid lubricant, which plays a lubricating role at the key parts, avoiding the problem of low lubricant utilization caused by the general lubrication mode of traditional liquid lubricating materials, and achieving fixed-point delivery of lubricants, which is beneficial to improving lubricant efficiency while reducing lubricant usage. In addition, the smooth outer shell layer can not only play a role in mechanical protection, enhanced dispersion, and control of lubricant release, but also play a certain role in ball lubrication when it is not broken.

[0028] The present invention utilizes the isolation of multi-layer shell materials to prevent a large amount of liquid lubricant from being directly mixed into the drilling fluid, thereby overcoming the problem of significantly increased foaming rate of the drilling fluid caused by hydrolysis of the liquid lubricant in the drilling fluid when the liquid lubricant is directly used.

[0029] In summary, the drilling composite lubricating material of the present invention can be fixedly attached to key parts with severe friction loss during the construction process to play a lubricating role, and can achieve dual protection of physical isolation and heat absorption and cooling of the core liquid lubricant through a multi-layer functional protection structure, alleviate the problem of rapid increase in foaming of the drilling fluid during the circulation process, and maintain excellent lubrication ability. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative labor.

[0031] Figure 1 It is a schematic diagram of the structure of the composite lubricating material for drilling of the present invention. DETAILED DESCRIPTION

[0032] The present invention is further described below in conjunction with the accompanying drawings and embodiments. It should be noted that, in the absence of conflict, the embodiments in this application and the technical features in the embodiments can be combined with each other. It should be noted that, unless otherwise specified, all technical and scientific terms used in this application have the same meanings as those generally understood by those of ordinary skill in the art to which this application belongs. The words "including" or "comprising" and the like used in the disclosure of the present invention mean that the elements or objects appearing before the word cover the elements or objects listed after the word and their equivalents, without excluding other elements or objects.

[0033] like Figure 1 As shown, the present invention provides a drilling composite lubricating material, including a core layer, a protective shell layer, a phase change layer and a smooth outer shell layer, which are sequentially wrapped from the inside to the outside to form a micron-sized sphere; the core layer is a liquid lubricant, the protective shell layer is an inorganic protective shell layer, the phase change layer is prepared by solid-liquid conversion phase change material, and the smooth outer shell layer is prepared by inert material.

[0034] In the above embodiments, the present invention uses multiple materials to wrap the liquid lubricant in multiple layers, which can achieve dual protection of mechanical isolation and heat absorption and cooling of the core liquid lubricant. The smooth outer shell layer made of inert material can prevent a large amount of liquid lubricant from mixing into the drilling fluid, maintain a low concentration of lubricating grease in the entire drilling fluid system, and avoid a large amount of liquid lubricant hydrolyzed in the drilling fluid, which causes a significant increase in the foaming rate of the drilling fluid. The phase change material is sandwiched between the inorganic protective shell layer and the smooth outer shell layer, which can prevent it from absorbing heat and converting it into a liquid state and then leaking into the drilling fluid or the lubricating liquid in the inner core. The rupture of the smooth outer shell layer of the composite material under a certain friction shear force can be used to achieve the fixed-point release of the lubricating material in the critical area of ​​high friction.

[0035] In the present invention, the smooth outer shell layer can not only play the role of protection and fixed-point rupture and release, but also play a certain lubrication effect through the ball action in some low-friction areas; the phase change material of the phase change layer can gradually transform into liquid in the high-temperature environment underground to absorb a large amount of heat, thereby preventing the liquid lubricant in the core layer from being too hot, resulting in a decrease in its lubrication performance. After circulating with the drilling fluid to the low-temperature environment on the ground, the phase change material can release the heat absorbed underground and transform back into a solid. In addition, after the smooth outer shell layer is broken, the phase change material can also play a certain lubrication and cooling role in the high-temperature friction part; the protective shell layer of the inner layer of the phase change layer can prevent the phase change material that absorbs heat and transforms into liquid during the circulation process from merging with the liquid lubricant in the core layer, thereby affecting the heat absorption and release performance of the phase change material; the liquid lubricant in the core layer is subject to multiple protections, and can maintain stable performance during the circulation of the drilling fluid, and achieve efficient lubrication in key areas when released under pressure.

[0036] When the present invention is used, the drilling composite lubricant is dispersed in the drilling fluid during the drilling operation, and circulates freely on the ground and underground with the drilling fluid. Due to the protection of the smooth outer shell layer, the liquid lubricant in the core layer will not have adhesion loss in the low friction or frictionless parts. When the drilling composite lubricant enters the high friction part and is subjected to strong extrusion and shearing, the smooth outer shell layer breaks, and the liquid lubricant in the core layer of the drilling composite lubricant material that maintains high performance is released to the high friction area at a high concentration, which plays a role in targeted lubrication and drag reduction. The isolation effect of the smooth outer shell layer prepared by the inert material is also conducive to maintaining the dispersibility of the liquid lubricant in the drilling fluid, reducing the probability of the liquid lubricant being hydrolyzed, thereby improving the utilization rate of the liquid lubricant. In addition, the smooth outer shell layer prepared by the inert material also avoids the core liquid lubricant from being directly mixed into the drilling fluid system. Therefore, the concentration of the lubricant in the drilling fluid is extremely low, which is not only conducive to reducing the loss of the liquid lubricant, but also prevents the concentration of the hydrolyzed liquid lubricant in the drilling fluid from being too high, resulting in a significant increase in the foaming rate of the drilling fluid. When reaching the high-temperature area underground, the phase change material in the drilling composite lubricant gradually transforms into a liquid state, and this process absorbs a large amount of heat; when circulating to the low-temperature area near the wellhead, the phase change material transformed into a liquid state releases heat and transforms into a solid again; the entire phase change heat absorption and release process can effectively alleviate the adverse effects of high temperature in deep wells on the performance of the liquid lubricant in the core layer of the drilling composite lubricant, enabling it to maintain excellent performance for a long time.

[0037] In a specific embodiment, the liquid lubricant is any one of modified vegetable oil lubricant, polyol ester lubricant, alcohol ether lubricant, phosphate ester lubricant, and mineral oil lubricant; the inorganic material of the inorganic protective shell is silicon dioxide or calcium carbonate; the solid-liquid conversion phase change material is any one of paraffin, fatty acid, polyol, molten salt, and hydrated salt; the inert material is any one of epoxy resin, vinyl ester resin, phenolic resin, urea-formaldehyde resin, melamine resin, polymethyl methacrylate, and natural polysaccharide derivatives.

[0038] It should be noted that the material types in the above embodiments are only preferred materials of the present invention. In addition to these materials, other similar materials in the prior art that can achieve the same effect can also be applied to the present invention.

[0039] In a specific embodiment, when the protective shell layer is a silica inorganic protective shell layer and the smooth shell layer is a urea-formaldehyde resin polymer shell layer, the drilling composite lubricating material is prepared by the following steps:

[0040] S1: 10-30 g of a liquid lubricant is mixed with 5-15 g of a tetraethyl silicate solution to obtain an oil phase, and the oil phase is added to 200-400 g of an ionic surfactant solution to react and obtain particles of the liquid lubricant coated with silica.

[0041] In a specific embodiment, the solvent of the tetraethyl silicate solution is dichloromethane with a concentration of 10%; the solute weight ratio of the ionic surfactant solution is 0.3-1%.

[0042] In a specific embodiment, when the reaction is carried out, the mixture is first stirred at a rotation speed of 1000-1500 r / min for 20-40 min, then heated to 40-50° C. and stirred for 1.5-3 h, then the pH value is adjusted to 2-3, and finally heated to 75-85° C. and stirred for 30 min to obtain the silica-coated liquid lubricant particles.

[0043] S2: subjecting the silica-coated liquid lubricant particles to a hydrophobic treatment to obtain silica-encapsulated particles having a hydrophobic surface.

[0044] In a specific embodiment, when performing the hydrophobic treatment, the particles are first soaked in a dichloromethane solution containing 10-25% silane coupling agent for 2-4 hours, then washed with an organic solvent, and dried to obtain the silica encapsulated particles having a hydrophobic surface.

[0045] It should be noted that the hydrophobic treatment is mainly to make the particles lipophilic, so that they are more easily adsorbed by the phase change material later. In addition to the hydrophobic treatment method of the above embodiment, other methods in the prior art that can make particles hydrophobic and lipophilic can also be applied to the present invention.

[0046] S3: Add 20-30 g of urea and 50-70 g of formaldehyde to 500 g of water, add triethanolamine dropwise to adjust the pH to 8-9, then heat in a water bath at 60-70° C. for 40-90 min, and cool to obtain a polymer shell prepolymer solution.

[0047] S4: heating the solid-liquid conversion phase change material to convert it into a liquid state to obtain a liquid phase change material; and placing the silicon dioxide encapsulated particles having a hydrophobic surface in the liquid phase change material, and ultrasonically dispersing to obtain a dispersion.

[0048] S5: spraying the dispersion into the polymer shell prepolymer solution by a droplet jetting method, and using the temperature of the polymer shell prepolymer solution to solidify the liquid phase change material and adhere to the surface of the silica encapsulated particles having a hydrophobic surface.

[0049] In the present invention, the droplet injection method can utilize high-speed airflow to blow the dispersion into tiny droplets and spray them into the polymer shell prepolymer solution. It should be noted that in order to accelerate the solidification rate of the liquid phase change material, it can also be solidified by cooling.

[0050] S6: adjusting the pH of the mixed solution obtained in step S5 to 3-4, then heating it at 50-70° C. with stirring for 2-5 hours, and washing it to obtain the drilling composite lubricating material.

[0051] In a specific embodiment, stirring is performed at a rotation speed of 800-1200 r / min; and during washing, anhydrous ethanol and deionized water are used in sequence for washing.

[0052] It should be noted that the above embodiment is only a preferred embodiment of the preparation method of the drilling composite lubricating material in which the protective shell layer is a silica inorganic protective shell layer and the smooth outer shell layer is a urea-formaldehyde resin polymer outer shell layer. Those skilled in the art can prepare the drilling composite lubricating material of the present invention using the existing technology based on the materials selected for each layer of the present invention and the four-layer structure of the drilling composite lubricating material of the present invention.

[0053] Example 1

[0054] A drilling composite lubricating material is prepared by the following steps:

[0055] (1) Preparation of micron-sized particles of polyol ester lubricant encapsulated with silica.

[0056] 20g of polyol ester lubricant is mixed with 10g of tetraethyl orthosilicate (TEOS) dissolved in dichloromethane (DCM) at a concentration of 10% as the oil phase. The oil phase is added to 300g of water containing 1% by weight of hexadecyl trimethyl ammonium bromide (CTAB), stirred at a speed of 1200r / min for 30min, and then heated to 40°C and stirred for 2h to form a phase-separated emulsion template. The pH value of the aqueous phase is adjusted to 3, and the reaction temperature is increased to 80°C to promote the hydrolysis and condensation reaction of TEOS at the oil-water interface, and stirring is continued for 30min to form micron-sized particles of polyol ester lubricant encapsulated in SiO2 shells. The reaction principle involved in this step is as follows:

[0057]

[0058] (2) Preparation of urea-formaldehyde resin prepolymer.

[0059] 25 g of urea and 65 g of formaldehyde were added to 500 g of deionized water, triethanolamine was added dropwise to adjust the pH to 8.5, and then the mixture was heated in a water bath at 65° C. for 60 min and cooled to obtain a urea-formaldehyde resin prepolymer solution.

[0060] (3) Surface hydrophobization and paraffin coating of SiO2 encapsulated particles.

[0061] The SiO2 encapsulated polyol ester lubricant micron-sized particles prepared in step (1) are immersed in a 20% tert-butyldimethylsilyl chloride (TBSCl) DCM solution for 2 hours, then taken out, washed with toluene and acetone, and dried. The reaction principle involved in this step is as follows:

[0062]

[0063] The paraffin phase change material is heated to convert it into a liquid state, and the SiO2 encapsulated particles treated with a TBSCl silane coupling agent for hydrophobization are placed in the molten liquid paraffin, and the dispersion is enhanced by ultrasound. Then, the dispersion is blown into tiny droplets by a high-speed airflow and sprayed into the urea-formaldehyde resin prepolymer solution obtained in step (2) by a droplet injection method, so that the liquid paraffin solidifies at a relatively low temperature and adheres to the particle surface.

[0064] (4) Urea-formaldehyde resin encapsulation.

[0065] The pH value of the urea-formaldehyde resin prepolymer solution sprayed with paraffin-coated particles was adjusted to 4.0, and then heated in a 60°C water bath for 3 hours and mechanically stirred at a speed of 900 r / min to complete the curing reaction of the urea-formaldehyde resin. Finally, it was washed with anhydrous ethanol and deionized water in turn to obtain the drilling composite lubricating material SS-1 with a four-layer structure. The reaction principle involved in this step is as follows:

[0066]

[0067] Example 2

[0068] A drilling composite lubricating material is prepared by the following steps:

[0069] (1) Preparation of micron-sized particles of polyol ester lubricant encapsulated with silica.

[0070] 15g of polyol ester lubricant was mixed with 10g of tetraethyl orthosilicate (TEOS) dissolved in dichloromethane (DCM) at a concentration of 10% as the oil phase. The oil phase was added to 300g of water containing 1% by weight of hexadecyl trimethyl ammonium bromide (CTAB), stirred at a speed of 1000r / min for 30min, and then heated to 45°C and stirred for 2h to form a phase-separated emulsion template. The pH value of the aqueous phase was adjusted to 3, and the reaction temperature was raised to 80°C to promote the hydrolysis and condensation reaction of TEOS at the oil-water interface, and stirring was continued for 30min to form micron-sized particles of polyol ester lubricant encapsulated in SiO2 shells.

[0071] (2) Preparation of urea-formaldehyde resin prepolymer.

[0072] 20 g of urea and 50 g of formaldehyde were added to 500 g of deionized water, triethanolamine was added dropwise to adjust the pH to 8.5, and then the mixture was heated in a water bath at 60° C. for 60 min and cooled to obtain a urea-formaldehyde resin prepolymer solution.

[0073] (3) Surface hydrophobization and paraffin coating of SiO2 encapsulated particles.

[0074] The SiO2 encapsulated polyol ester lubricant micron-sized particles prepared in step (1) were immersed in a 20% tert-butyldimethylsilyl chloride (TBSCl) DCM solution for 2 hours, then taken out, washed with toluene and acetone, and dried.

[0075] The paraffin phase change material is heated to convert it into a liquid state, and the SiO2 encapsulated particles treated with a TBSCl silane coupling agent for hydrophobization are placed in the molten liquid paraffin, and the dispersion is enhanced by ultrasound. Then, the dispersion is blown into tiny droplets by a high-speed airflow and sprayed into the urea-formaldehyde resin prepolymer solution obtained in step (2) by a droplet injection method, so that the liquid paraffin solidifies at a relatively low temperature and adheres to the particle surface.

[0076] (4) Urea-formaldehyde resin encapsulation.

[0077] The pH value of the urea-formaldehyde resin prepolymer solution sprayed with paraffin-coated particles was adjusted to 4.0, and then heated in a 70°C water bath for 3 hours and mechanically stirred at a speed of 900 r / min to complete the curing reaction of the urea-formaldehyde resin. Finally, it was washed with anhydrous ethanol and deionized water in turn to obtain the drilling composite lubricating material SS-2 with a four-layer structure.

[0078] Example 3

[0079] Different from Example 1, the phase change material used in step (3) of this example is pentaerythritol, and a drilling composite lubricating material SS-3 with a four-layer structure is obtained.

[0080] Example 4

[0081] Different from Example 1, the liquid lubricant used in step (1) of this example is a phosphate ester lubricant, and a drilling composite lubricating material SS-4 with a four-layer structure is obtained.

[0082] Comparative Example 1

[0083] This comparative example uses only the core liquid lubricant, that is, directly uses the polyol ester lubricant without being encapsulated by any shell layer (material), which is recorded as lubricating material DB-1.

[0084] Comparative Example 2

[0085] This comparative example does not have the SiO2 inorganic protective shell layer in the four-layer structure. 20g of liquid polyol ester lubricant and 5g of paraffin were mixed and directly dispersed in the urea-formaldehyde resin prepolymer solution, and packaged according to the urea-formaldehyde resin packaging method described in Example 1 to obtain lubricating material DB-2.

[0086] Comparative Example 3

[0087] This comparative example does not have a phase change layer in the four-layer structure. After preparing silicon dioxide encapsulated polyol ester lubricant micron particles according to the method in Example 1, the steps of surface hydrophobization and paraffin coating of SiO2 encapsulated particles were skipped, and urea-formaldehyde resin encapsulation was directly performed to obtain lubricating material DB-3.

[0088] Comparative Example 4

[0089] This comparative example does not have a smooth outer shell layer in the four-layer structure. According to the method in Example 1, silicon dioxide encapsulated polyol ester lubricant micron particles were prepared, and after being wrapped with paraffin, the urea-formaldehyde resin encapsulation step was skipped to directly complete the preparation to obtain lubricating material DB-4.

[0090] Test Case

[0091] 3% bentonite, 0.1% Na2CO3, 2% anti-slump filter loss agent, 3% sulfomethyl phenolic resin, 2% lignite resin and barite were added into tap water, stirred at 1000r / min for 20min, and then sealed and cured at 25℃±1℃ for 24h to obtain a density of 1.94g / cm 3 The water-based drilling fluid slurry was prepared, and 3% of the lubricating materials of the above embodiments and comparative examples were added to the water-based drilling fluid slurry, and the foaming of the above embodiments and comparative examples was observed after stirring at 1500r / min for 10 minutes. The apparent viscosity increase value, density change value and lubrication coefficient reduction rate of the above embodiments and comparative examples were tested with reference to the Chinese standard Q / SY 17088-2016 "Technical Specifications for Liquid Lubricants for Drilling Fluids". The experimental results are shown in Table 1:

[0092] Table 1 Performance indicators of lubricating materials at room temperature

[0093] name Foaming Apparent viscosity increase (mPa·s) <![CDATA[Density change value (g / cm 3 )]]> Lubrication coefficient reduction rate (%) Example 1 No bubbles -1 -0.02 55 Example 2 No bubbles 0 0.02 53 Example 3 No bubbles 0 0.01 54 Example 4 No bubbles -1 -0.01 58 Comparative Example 1 A small amount of bubbles 2 -0.02 31 Comparative Example 2 No bubbles -1 -0.01 49 Comparative Example 3 No bubbles 0 0.01 57 Comparative Example 4 No bubbles 4 -0.02 43

[0094] The drilling fluids mixed with lubricating materials were placed in an aging tank, aged at 160°C for 1 hour, then taken out, and then cooled at room temperature for 1 hour. The above heating aging-cooling was repeated 8 times and then taken out from the aging tank. After the drilling fluid temperature was cooled to room temperature, it was stirred at 1500r / min for 10 minutes, and the foaming of the above embodiments and comparative examples was observed. The apparent viscosity increase value, density change value and lubrication coefficient reduction rate of the above embodiments and comparative examples were tested with reference to the Chinese standard Q / SY17088-2016 "Technical Specifications for Liquid Lubricants for Drilling Fluids". The experimental results are shown in Table 2:

[0095] Table 2 Performance indicators of lubricating materials after 160℃ hot rolling aging cycle

[0096] name Foaming Apparent viscosity increase (mPa·s) <![CDATA[Density change value (g / cm 3 )]]> Lubrication coefficient reduction rate (%) Example 1 No bubbles -1 -0.01 56 Example 2 No bubbles 1 0.02 55 Example 3 No bubbles -1 -0.01 58 Example 4 No bubbles -1 -0.01 51 Comparative Example 1 More bubbles 1 -0.02 26 Comparative Example 2 No bubbles 0 0 43 Comparative Example 3 No bubbles 1 0.02 42 Comparative Example 4 No bubbles 2 0.01 39

[0097] It can be seen from Tables 1 and 2 that the presence of the shell material can improve the lubrication performance of the drilling fluid and inhibit the foaming problem of the drilling fluid. In addition, the drilling composite lubricating material must ensure a complete four-layer structure to effectively maintain the lubrication performance of the lubricating material after hot rolling cycle aging.

[0098] It should be noted that the above embodiments are only partial embodiments of the present invention. The drilling composite lubricating material of the present invention, which is formed by other materials and includes a core layer, a protective shell layer, a phase change layer and a smooth outer shell layer, which are wrapped in sequence from the inside to the outside to form a micron-sized sphere, has similar properties to the above embodiments, and is superior to single liquid lubricants and composite lubricating materials without a four-layer structure.

[0099] In summary, the present invention utilizes the four-layer structure of the drilling composite lubricating material to enable it to be fixedly attached to key parts with severe friction loss to exert lubrication, and can maintain low foaming and high lubricity after repeatedly entering the underground high-temperature environment. Compared with the prior art, the present invention has significant progress.

[0100] The above description is only a representative embodiment of the present invention and does not limit the present invention in any form. Any technician familiar with the profession, without departing from the scope of the technical solution of the present invention, uses the above-disclosed technical contents to make some changes or modifications to the embodiments are equivalent embodiments of the present invention. However, any simple modification, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention still fall within the scope of the technical solution of the present invention.

Claims

1. A composite lubricating material for drilling, characterized in that: It includes a core layer, a protective shell layer, a phase change layer and a smooth outer shell layer which are sequentially wrapped from the inside to the outside to form a micron-sized spherical object; The core layer is a liquid lubricant, the protective shell layer is an inorganic protective shell layer, the phase change layer is made of a solid-liquid conversion phase change material, and the smooth outer shell layer is made of an inert material.

2. The drilling composite lubricating material according to claim 1, characterized in that: The liquid lubricant is any one of modified vegetable oil lubricant, polyol ester lubricant, alcohol ether lubricant, phosphate ester lubricant and mineral oil lubricant.

3. The composite lubricating material for drilling according to claim 1, characterized in that: The inorganic material of the inorganic protective shell layer is silicon dioxide or calcium carbonate.

4. The drilling composite lubricating material according to claim 1, characterized in that: The solid-liquid conversion phase change material is any one of paraffin, fatty acid, polyol, molten salt and hydrated salt.

5. The composite lubricating material for drilling according to claim 1, characterized in that: The inert material is any one of epoxy resin, vinyl ester resin, phenolic resin, urea-formaldehyde resin, melamine resin, polymethyl methacrylate, and natural polysaccharide derivatives.

6. The composite lubricating material for drilling according to any one of claims 1 to 5, characterized in that: When the protective shell layer is a silicon dioxide inorganic protective shell layer and the smooth outer shell layer is a urea-formaldehyde resin polymer outer shell layer, the drilling composite lubricating material is prepared by the following steps: S1: 10-30 g of a liquid lubricant is mixed with 5-15 g of a tetraethyl silicate solution to obtain an oil phase, and the oil phase is added to 200-400 g of an ionic surfactant solution to react to obtain particles of the liquid lubricant coated with silica; S2: subjecting the silica-coated liquid lubricant particles to a hydrophobic treatment to obtain silica-encapsulated particles having a hydrophobic surface; S3: adding 20-30 g of urea and 50-70 g of formaldehyde to 500 g of water, dropping triethanolamine to adjust the pH to 8-9, then heating in a water bath at 60-70° C. for 40-90 min, and cooling to obtain a polymer shell prepolymer solution; S4: heating the solid-liquid conversion phase change material to convert it into a liquid state to obtain a liquid phase change material; placing the silicon dioxide encapsulated particles having a hydrophobic surface in the liquid phase change material, and ultrasonically dispersing to obtain a dispersion; S5: spraying the dispersion into the polymer shell prepolymer solution by a droplet jetting method, and using the temperature of the polymer shell prepolymer solution to solidify the liquid phase change material and adhere to the surface of the silica encapsulated particles having a hydrophobic surface; S6: adjusting the pH of the mixed solution obtained in step S5 to 3-4, then heating it at 50-70° C. with stirring for 2-5 hours, and washing it to obtain the drilling composite lubricating material.

7. The composite lubricating material for drilling according to claim 6, characterized in that: In step S1, the solvent of the tetraethyl silicate solution is dichloromethane, and the concentration is 10%.

8. The composite lubricating material for drilling according to claim 6, characterized in that: In step S1, the solute weight ratio of the ionic surfactant solution is 0.3-1%.

9. The composite lubricating material for drilling according to claim 6, characterized in that: In step S1, when reacting, first stir at a rotation speed of 1000-1500 r / min for 20-40 min, then heat to 40-50° C. and stir for 1.5-3 h, then adjust the pH value to 2-3, and finally heat to 75-85° C. and stir for 30 min to obtain the silica-coated liquid lubricant particles.

10. The composite lubricating material for drilling according to claim 6, characterized in that: In step S6, stirring is performed at a rotation speed of 800 to 1200 r / min; during washing, anhydrous ethanol and deionized water are used in sequence for washing.

Citation Information

Patent Citations

  • Method for preparing novel solid lubricant microspheres for drilling fluid

    CN101705079A

  • Nano lubricant used for drilling fluid, and preparation method thereof

    CN105331337A

  • Preparation method for novel nano lubricant for drilling fluid

    CN107858139A

  • Environment-friendly oil bag lubricant for drilling fluid and preparation method of environment-friendly oil bag lubricant

    CN109796944A

  • High-temperature-resistant saturated-salt-resistant lubricant for drilling fluid and preparation method thereof

    CN111676001A

Cited By

  • 200 DEG C-resistant salt-resistant temperature-responsive cementing wall-fixing agent for water-based drilling fluid as well as preparation method and application of cementing wall-fixing agent

    CN121406299A